2009
DOI: 10.1111/j.1651-2227.2009.01508.x
|View full text |Cite
|
Sign up to set email alerts
|

The transient value of classifying preschool wheeze into episodic viral wheeze and multiple trigger wheeze

Abstract: When children with preschool wheeze are classified into episodic (viral) wheeze or multiple trigger wheeze based on retrospective questionnaire, the classification is likely to change significantly within a 1-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 28 publications
4
75
1
5
Order By: Relevance
“…The group agreed that the distinction between EVW and MTW is not as clear-cut as the 2008 report may have suggested, and that it changes over time in many children [15]. Despite significant differences in clinical presentation, lung function and genetics between children with EVW and MTW phenotypes, there is a large overlap between the groups [16][17][18][19].…”
Section: Distinguishing Between Evw and Mtwmentioning
confidence: 88%
See 1 more Smart Citation
“…The group agreed that the distinction between EVW and MTW is not as clear-cut as the 2008 report may have suggested, and that it changes over time in many children [15]. Despite significant differences in clinical presentation, lung function and genetics between children with EVW and MTW phenotypes, there is a large overlap between the groups [16][17][18][19].…”
Section: Distinguishing Between Evw and Mtwmentioning
confidence: 88%
“…Despite significant differences in clinical presentation, lung function and genetics between children with EVW and MTW phenotypes, there is a large overlap between the groups [16][17][18][19]. While some children retain a consistent pattern of EVW or MTW over longer periods, symptom patterns change over time in many [15]. The underlying airway pathology remains unclear in many preschool children with recurrent troublesome wheeze and this hinders the choice of the most effective controller therapy.…”
Section: Distinguishing Between Evw and Mtwmentioning
confidence: 97%
“…These differences in lung function support the notion that different phenotypes, such as EVW and MTW, can be distinguished within the whole group of preschool children with wheezing. However, it has been demonstrated that wheezing phenotypes in young children are unstable over time, and that individual patients may change from EVW to MTW and vice versa [3]. Whether such changes are accompanied by changes in lung function remains to be seen.…”
Section: Preschool Wheezementioning
confidence: 99%
“…31,32 The common clinical scenario of 'wheezy infants' poses a particular challenge for primary care. The diagnosis is based on the history, signs and symptoms, 33,34 and whilst the presence of atopy may strengthen the probability of asthma, diagnostic spirometry is not practical under the age of 5 years. 35 The IPCRG guidelines suggest a range of symptom-based tools and investigations including peak flow monitoring, spirometry, reversibility testing and challenge tests, 36 and a recent international statement summarises the technical details.…”
Section: Diagnosismentioning
confidence: 99%